Factors deterring and prompting the decision to attempt suicide on the railway networks: findings from 353 online surveys and 34 semi-structured interviews. (October 2019) - Marzano, Lisa; Mackenzie, Jay-Marie; Kruger, Ian; Borrill, Jo; Fields, Bob
Abstract : Background: There is a suicide on the British railways every 36 hours. However, the reasons why people choose to die by train are not well understood. Aims: To explore factors influencing and discouraging the decision to attempt suicide on the railway networks. Method: We conducted an online survey and qualitative interviews with individuals who had contemplated or attempted suicide by train. Results: A total of 353 survey responders had considered and 23 had attempted suicide at rail locations (including railways and metro/underground); a third of these cases were impulsive. The most frequently reported motivations for contemplating or attempting suicide were perceptions of quick and certain lethality (54 and 37%, respectively) and easy access to rail settings (33 and 38%, respectively). The main factor discouraging people from rail suicide was its wider impact, especially on train drivers (19%). In qualitative interviews ( N = 34) the desire to avoid intervention from others was also a common motivating factor for attempting suicide on the railway networks. Conclusions: People attempt suicide by train because railway settings are easy to access and because of an inaccurate perception of certain and quick lethality. Tackling exaggerated perceptions of lethality may help reduce suicides by train. Declaration of interest: None.